COMPETENCY-BASED APPROACH: TRANSFORMING ASSESSMENT IN EDUCATION - Islyamova Soniya Yunusovna (Web of Journals Publishing, 2025)
This article discusses the growing popularity of the competency-based approach in education, which which emphasizes students' demonstration of their skills and knowledge rather than the formal completion of academic courses. Strategies for rethinking assessment are discussed, aimed at accurately reflecting learners' competencies in real-life situations, as well as methods that foster a deeper understanding of learners' competencies and knowledge. As well as methods that promote a deeper understanding of their abilities and readiness for professional practice.
Keywords: Competency-based approach, education, skills, knowledge, assessment, competencies, formative process, educational strategies, engagement, professional practice.